A LOVING GREETING FROM NIAS: THE MEANING, FUNCTION, AND SOCIAL VALUES IN THE WORD YA’AHOWU - Darmawan Harefa (Universitas Nias Raya, 2025)
The word Ya’ahowu is a distinctive greeting used by the people of Nias, carrying deep meaning and strong cultural values. This study aims to explore the meaning, function, and social significance of Ya’ahowu as a symbol of love and cultural identity within the Nias community. The research employs a literature review method, analyzing various sources such as journals, books, and scholarly articles related to the language and culture of Nias. The findings reveal that Ya’ahowu is not merely a simple salutation but embodies a prayer and well-wishes for the person being greeted. Its primary functions extend beyond social interaction, encompassing cultural and emotional roles that strengthen interpersonal relationships and foster social solidarity. Moreover, Ya’ahowu reflects core values such as affection, respect, and a strong spirit of brotherhood. In today’s modern context, this greeting remains relevant and holds potential as a symbol of cultural diplomacy and a tool for preserving the local language. In conclusion, Ya’ahowu is an important intangible cultural heritage that must be preserved. It serves not only as a means of communication but also as a representation of the unique values of love and peace inherent to the Nias people.